Distribution of Sri Lanka Dull-blue Flycatcher (Eumyias sordidus) in the Horton Plains National Park - Dharmarathne, W.D.S.C.; Mahaulpatha, W.A.D (My University, 2017)
attached

Distribution of the Sri Lanka Dull-blue Flycatcher (Eumyias sordidus) was studied at Horton Plains National Park, from September 2015 to May 2016. Three main habitats were identified as Cloud Forest habitat, Cloud Forest Die-back habitat and Grassland habitat. Line transact method was used. Birds were recorded on three consecutive days in each month while travelling along these transacts. About 104 individuals were recorded from the Cloud Forest habitat, 60 individuals from the Cloud Forest Die-back habitat and 2 individuals were recorded from the Grassland habitat. Relative abundance of the E. sordidus was 2.3% in the cloud Forest habitat and they were the ninth abundant species in that habitat. In the Cloud Forest Die-back habitat relative abundance of E. sordidus was 3.21% and it was the sixth abundant species. In the Grassland habitat the relative abundance of E. sordidus was 0.07% and it was twenty seventh abundant species. Present study revealed that Cloud Forest is the preferred habitat of E. sordidus in the Horton Plains National Park.
Keywords: Sri Lanka Dull-blue Flycatcher; endemic birds; Horton Plains; distribution